Radio Sensitivity of the winter and spring barley varieties according to the morphological efect of low-dose gamma irradiation on the original seeds. - Е. А. Kazakova; Е. S. Makarenko; М. S. Podlutsky; A. A Dontsova; S. V. Bitarishvili; M. A. Lychenkova; I. V. Gorbatova; Е. G. Filippov; D. P. Dontsov; Т. V. Chizh; А. S. Snegirev; P. Yu. Volkova (Зерновое хозяйство России)
Barley is the main forage crop in the Russian Federation. Barley grain is also used for food and brewery (Filippov, 2013). It is common knowledge that low doses of gamma irradiation can have a stimulating effect on the growth and development of plants, in particular barley. However, there is a lack of knowledge about the molecular pathways responsible for the formation of the stimulation effect after low-dose seed irradiation. The use of varieties with different radio sensitivity to low-dose gamma irradiation will allow studying specific molecular mechanisms to form a stimulating irradiation effect. Such knowledge could further help in the development of varieties with a large stable productivity over the years and with high resistance to biotic and abiotic stressors. In 2019 there was conducted a gamma irradiation of the original seeds of nine winter and spring barley varieties developed in the FSBSI “Agricultural Research Center “Donskoy” in order to assess intensity of the response on low-dose ionizing irradiation based on changes in the morphological parameters of irradiated and unirradiated plants. The original seeds of each barley variety were irradiated at the FSBSI “All-Russian Research Institute of Radiology and Agroecology” by the gamma device “GUR-120” with 60Со radiation sources at a dose of 20 Gy (dose rate of 60 Gy/hour). The statistical data processing was performed by the Microsoft Office Excel 2019. The morphological analysis of the length and weight of roots and sprouts made it possible to establish the presence or absence of the stimulating irradiation effect on the studied indicators of the varieties and to conduct their subsequent ranking according to the value of the radiobiological effect. There have been identified the winter and spring barley varieties with different sensitivity to a dose of 20 Gy. The stimulating irradiation effect was established in such varieties as “Foks 1”, “Ratnik”, “Yerema” and “Master”. The variety “Leon” had an inhibitory irradiation effect.